Improving the Wellbeing of Students Based on Infrastructure Management in Al Anwar Mranggen Islamic Boarding School - Novi Fitriana; Vida Affana; Zulfida Aulia Fatimah (Yayasan Vifada Cendikia Indonesia, 2026)
This study aims to examine how educational facilities and infrastructure management contributes to improving students' well-being at Pondok Pesantren Putri Al-Anwar Mranggen. A qualitative descriptive approach was employed using a case study design. Data were collected through in-depth interviews, participant observation, and document analysis involving the pesantren leader, facilities management staff, teachers, and students. The collected data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing, while source and technique triangulation were applied to ensure data credibility. The findings indicate that effective management of educational facilities through systematic planning, procurement, supervision, and utilization creates a supportive learning environment that enhances students' physical comfort, psychological well-being, and spiritual development. Active participation of school stakeholders and continuous monitoring further strengthen the sustainability and effectiveness of facilities management. These findings demonstrate that educational facilities management extends beyond administrative functions and serves as a strategic approach to fostering holistic student well-being in Islamic boarding schools. The study provides practical implications for pesantren administrators and education policymakers in developing sustainable facilities management systems and recommends further research in different educational contexts to examine the relationship between facilities management and student well-being.